Motivations and Effects of Mergers and Acquisitions on the Warsaw Stock Exchange, Considering ESG Factors - Zabawa, Justyna; Łosiewicz-Dniestrzańska, Ewa; Radło, Mariusz-Jan; Napiórkowski, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2025)
The main purpose of this article is to determine the impact of Environmental, Social, and Governance (ESG) factors on corporate mergers and acquisitions (M&A). The study was conducted on companies listed on the Warsaw Stock Exchange (WSE), which plays a significant role in European capital markets, particularly in the Central and Eastern European (CEE) region. It is the largest stock exchange in the region by both market capitalisation and the number of listed companies. Data for the study were collected in 2024 using CATI (Computer-Assisted Telephone Interviewing) and CAWI (Computer-Assisted Web Interviewing) methods from companies that had conducted M&A in the previous five years. Data analysis was performed using descriptive statistics and several tests, including ANOVA, Kolmogorov-Smirnov, Shapiro–Wilk, Levene, Welch and Kruskal-Wallis. The study investigated the motives for companies to consider ESG factors when conducting M&A transactions. The results show that WSE companies consider managerial awareness to have the greatest influence on the inclusion of these factors in M&A. Detailed information was obtained on the different motivations of listed companies to include ESG factors in M&A transactions and the subsequent impact of these transactions on their financial performance. Additionally, the study investigated the impact of company size and capital ownership on decisions to include ESG factors in M&A. The results offer an important contribution to existing research on M&A in the CEE region.